MENAJEMEN SEKOLAH KHUSUS OLAHRAGAWAN INTERNASIONAL - Sunu, La; Asbas, Andi Ichrar; Labulan, Labulan (JMSP (Jurnal Manajemen dan Supervisi Pendidikan), 2016)
Abstract:the purpose of this study is to determine: (1) the recruitment of students / athletesSKOI, (2) the learning process of students / athletes SKOI, (3) the results of NationalExamination student / athletes SKOI. (4) the results of achievements at local, national, andinternational student / athletes SKOI, (5) barriers and solutions of the students / athletes SKOI.The approach used is qualitative method by using data collection techniques are observation.The results of the research is the process of admission of students / athletes by letter callsfrom diknas cities and counties. Learning process by using the same curriculum 2006 regularschools, but in practice there are some differences. The results of both semester exams andpassing the national exam 100%. Sporting achievements championship results obtained inthe national and international scale. Barriers faced is the lack of socialization with the district/ city, teaching hours, in contrast to regular schools, the semester schedule sometimes clashwith the event and national exams, as well as the lack of tournaments between students andthe lack of involvement in national and international championships.Keywords: school management, special school, athlete schoolAbstrak: tujuan penelitian ini adalah untuk mengetahui: (1) rekrutmen siswa/atlit SKOI,(2) proses pembelajaran siswa/atlit SKOI, (3) hasil Ujian Nasional siswa/atlit SKOI. (4)hasil prestasi daerah, nasional, dan internasional siswa/atlit SKOI, (5) hambatan dan solusiyang dimiliki siswa/atlit SKOI. Pendekatan yang digunakan yaitumetode kualitatif denganmenggunakan teknik pengumpulan data yaitu observasi.Hasil penelitian yaitu prosespenerimaan siswa/atlit dengan melalui surat panggilan dari diknas kota dan kabupaten. Prosespembelajaran dengan menggunakan kurikulum tahun 2006 sama sekolah reguler, namundalam pelaksanaannya ada beberapa perbedaan. Hasil ujian semester baik dan kelulusanujian nasional 100%. Prestasi olahraga hasil kejuaraan diperoleh dalam skala nasional daninternasional. Hambatan yang dihadapiyaitu kurangnya sosialisasi dengan kabupaten/kota,jam belajar berbeda dengan sekolah reguler, jadwal semester terkadang benturan denganacara dan ujian nasional, serta minimnya turnamen antar pelajar dan kurangnyaketerlibatandalam kejuaraannasional dan internasional.Kata kunci: manajemen sekolah, sekolah khusus, sekolah olahragawan